2002
DOI: 10.1108/10662240210430892
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural dimensions of Internet portals

Abstract: When new technologies become available and cultures adopt them, the result can be either convergence, cultures becoming more similar as a result, or divergence, when cultures adopt technology in different ways that maintain or even further accentuate their differences. An analysis of full‐service national Web portals from different countries, typically offering a search engine, directories of links on a set of selected topics, news items (including weather, sports, entertainment, and stock market results), adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 8 publications
2
25
1
1
Order By: Relevance
“…While the results of this study confirm the results of other studies that included Arab countries [2,17], in regard to the use of culturally favored colors and depiction of images, they also refute the results of other studies, for example, Callahan [3], in regards to the presence of search engines and page orientation. The differences in the results could be attributed to the difference in country selection or website genre, therefore further research is needed.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…While the results of this study confirm the results of other studies that included Arab countries [2,17], in regard to the use of culturally favored colors and depiction of images, they also refute the results of other studies, for example, Callahan [3], in regards to the presence of search engines and page orientation. The differences in the results could be attributed to the difference in country selection or website genre, therefore further research is needed.…”
Section: Discussioncontrasting
confidence: 73%
“…Zahir, Dobbing, and Hunter [17] selected national web portals also from two countries, Egypt and Morocco. Their results showed that websites from Egypt had a strong focus on the Egyptian culture, reflecting a high Power Distance characteristic.…”
Section: Arab Countries In Cultural Design Studiesmentioning
confidence: 99%
“…Community was found to be significant for Korean respondents but not for the US respondents, similar to the finding of Zahir et al (2002) for Indonesians and Australians. Initially this seemed to be an unusual finding; however, if one considers the relatively recent advent of social sites such as MySpace and Facebook and then the interest in video communities via YouTube and TV via formats such as CNN's IReports then a plausible explanation surfaces.…”
Section: Findings and Discussionsupporting
confidence: 84%
“…Mega portals developed in different countries may have different characteristics depending on the particular culture (Zahir et al, 2002) and different macro-level services that satisfy the portals' users. The objective of this study is to analyze and compare the impact of service functions on the portal users' satisfaction in two different countries -Korea and the USA.…”
Section: Introductionmentioning
confidence: 99%
“…The Arabic-speaking region comprised Egypt, Lebanon, Libya, Kuwait, Iraq, Saudi Arabia and the United Arab Emirates. This group has been frequently applied in cross-cultural interface design studies to different extents (Barber & Badre, 1998;Callahan, 2007;Zahir, Dobing, & Hunter, 2002). However, grouping the seven countries into one group, excluding the rest of Arab countries, and assuming that Arab users have similar needs, expectations, and preferences on the web, without acknowledging possible individual differences across countries, can create potential problems in Arabic interface localization.…”
Section: Introductionmentioning
confidence: 99%